IMPLEMENTASI SISTEM PEMBELIAN BBM MELALUI APLIKASI MYPERTAMINA DITINJAU DARI PERSPEKTIF GOOD CORPORATE GOVERNANCE - Subairi, Imam; Prabowo, Bagya Agung (Kertha Semaya : Journal Ilmu Hukum, 2023)
This study aims to determine the application of the fuel purchase system through MyPertamina application, and the role of the government in realizing Good Corporate Governance, and how community influences use of MyPertamina Application in purchasing fuel. PT. Pertamina (Persero) is a state-owned company that has just launched an application called “MyPertamina” with the aim of increasing the decision to purchase fuel through various promotions offered through MyPertamina Application. This research uses juridical-sociological research methods with a regulatory and comparative approach. Furthermore, the implementation of the fuel purchase system through MyPertamina Application is able to have a positive and effective impact. In addition, the difficulty of the community in accessing and the need for community habits and the role of the government in providing ease of access, and the problem can be solved effectively.